Reinterpretasi Wali Adhal oleh Hakim Pengadilan Agama Metro dalam Penetapan Nomor 13/Pdt.P/2025/PA.Mt - Siti Setia Ningsih; Nency Dela Oktora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
This study analyzes the reinterpretation of the obstinate guardian (wali adhal) in the context of legal pluralism, with reference to the Number 13/Pdt.P/2025/PA.Mt at the Metro Religious Court, where his brother, as a guardian, refused to marry his younger sister who was Muslim. The purpose of this study is to formulate a reinterpretation of wali adhal that accommodates the two legal systems within the framework of rechtsvinding (legal discovery). Using empirical legal methods with a qualitative approach through the study of determination documents, in-depth interviews with judges, and customary stakeholders. The results of the study show that the judge reinterpreted wali adhal from a textual-procedural approach to a substantive-teleological approach by operationalizing maqashid al-sharia, hifzh an-nasl (protection of lineage and dignity), and sadd al-dzari’ah (closure of the path of damage). Judges apply rechtsvinding by integrating the principles of non-discrimination and gender equality, establishing guardianship as a legal solutions that protect women’s rights. The judge positioned Islamic law as the primary legal framework, customary law as a cultural consideration, and human rights as a constitutional safeguard in resolving normative conflicts. This research provides a theoretical contribution in the form of an analytical framework of legal pluralism in the jurisprudence of wali adhal, as well as a practical contribution in the form of a foundation for religious courts in handling similar cases in plural areas.